Bioleaching of Black Shale by Acidithiobacillus ferrooxidans - Anjum, Fozia; Nawaz Bhatti, Haq; Ambreen, Anila (Asian Journal of Chemistry, 2010)
Microbiological leaching has been used as an alternative approach to conventional hydrometallurgical methods of metals extraction. The main concern of the present study was to develop a feasible and economical technique to microbially recover metals such as Fe, U, Mo, Cu and Mn from black shale ore as well as to study the comparative growth of bacteria in a medium containing salts and ferrous sulphate. The microorganism used in this study was potentially important bacteria like Acidithiobacillus ferrooxidans, utilizing energy from the oxidation of ferrous iron, sulphur and reduced sulphur compounds. During bioleaching study, bacteria oxidize pyritic phase to ferric iron and sulphuric acid in case of samples supplemented with FeSO4. The pH of the media decreased and redox potential remarkably increased. In bioleached residues, K-jarosite and gypsum were predominant minerals and phologopite grades to biotite. Dolomite transformed to gypsum. Shake flask technique is feasible as bacterial leaching system.